2005
DOI: 10.1007/s10854-005-0543-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural, electrical and optical properties of copper selenide thin films deposited by chemical bath deposition technique

Abstract: A low cost chemical bath deposition (CBD) technique has been used for the preparation of Cu 2-x Se thin films on glass substrates. Structural, electrical and optical properties of these films were investigated. X-ray diffraction (XRD) study of the Cu 2-x Se films annealed at 523K suggests a cubic structure with a lattice constant of 5.697Å. Chemical composition was investigated by X-ray photoelectron spectroscopy (XPS). It reveals that absorbed oxygen in the film decreases remarkably on annealing above 423K. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 26 publications
(46 reference statements)
3
21
0
2
Order By: Relevance
“…The relation of the optical gap with the band structure is still controversial, given that only recently more reliable calculations of the band--structure in some of these copper chalcogenides could be carried out. Typically, it is assumed that these materials show an indirect band--gap, mainly based on the square--root energy dependence of the absorption coefficient, as found by Al Mamum et al [42,43] for Cu2--xSe and [44] for Cu2S. However, the magnitude of this coefficient is very large, and comparable to that of direct--gap semiconductors.…”
Section: Bulk Chalcogenide Semiconductorsmentioning
confidence: 99%
“…The relation of the optical gap with the band structure is still controversial, given that only recently more reliable calculations of the band--structure in some of these copper chalcogenides could be carried out. Typically, it is assumed that these materials show an indirect band--gap, mainly based on the square--root energy dependence of the absorption coefficient, as found by Al Mamum et al [42,43] for Cu2--xSe and [44] for Cu2S. However, the magnitude of this coefficient is very large, and comparable to that of direct--gap semiconductors.…”
Section: Bulk Chalcogenide Semiconductorsmentioning
confidence: 99%
“…The average crystal size values are approximately 40 nm for both Cu 3 Se 2 and CuSe thin films. Thin films of cubic Cu 2x Se and tetragonal Cu 3 Se 2 have been prepared by adjusting the bath parameters like pH, temperature and the ratio between copper and selenium ions in the reaction bath [184,185].…”
Section: Copper Selenide (Cuse)mentioning
confidence: 99%
“…From the table, the resistivity, carrier concentration and mobility of the Cu 0.87 Se thin films coated at 300, 400 and 500°C of this work is comparable with the values reported by the earlier workers. Table 3 reveals that non-stoichiometric (Cu 2-x Se) thin films show lower resistivity in the order of 10 -3 -10 -4 X cm, but the stoichiometric copper selenide (CuSe, Cu 2 Se) thin films shows resistivity in the order of 10 1 -10 -1 except CuSe (1.6 9 10 -3 ) thin film prepared by Gosavi RT (70 W ** ) C u 2-x Se 4.75 9 10 -4 2.3 9 10 21 5.5 [26] RT (90 W ** ) C u 2-x Se 3.94 9 10 -4 5.0 9 10 21 2.5 [26] RT (110 W ** ) C u 2-x Se 1.08 9 10 -3 1.3 9 10 21 4.5 [26] PLD RT Cu 1.7 Se -1.4 9 10 22 2.0 [24] CBD RT annealed at 250 Cu 2-x Se 0.5 9 10 -4 1.5 9 10 -4 -- [ 7] 90-95 Cu 2-x Se(x = 0.1) 0.1-2 9 10 -2 -- [ 11] MCBD RT Cu 2 Se *10 -1 -- [ 10] Solution growth RT CuSe 1.6 9 10 -3 -- [ 8] RT CuSe -7-10 9 10 21 0.5-2.5 [9] AACVD 400 450 Cu PLD pulsed laser deposition, CBD chemical bath deposition, MCBD modified chemical bath deposition, AACVD aerosol-assisted chemical vapor deposition, EPD electrophoretic deposition * T s -Substrate temperature ** Sputtering power Structural, morphological, optical and electrical properties of Cu 0.87 Se thin films coated……”
Section: Resultsmentioning
confidence: 99%
“…Okimura et al [6] prepared Cu 2-x Se-Si junction by conventional vacuum evaporation method and reported that the conversion efficiency of the junction is about 8.3 and 8.8 % for 3-and 2-mm-diameter Cu 2-x Se layer, respectively. Several chemical and physical methods such as chemical bath [2,[7][8][9][10][11], aerosol-assisted chemical vapor deposition [12,13], electroless [14], solgel [15], electrochemical deposition [16], electrophoretic deposition [17], brush electroplate deposition [18], cathodic deposition [19], dip coating [20], spray pyrolysis [21], vacuum co-evaporation [22], vacuum evaporation [6,23], pulsed laser deposition [4,24], selenization [25], magnetron sputtering [26], flash evaporation [27] and reactive evaporation [28] methods have been employed to deposit copper selenide thin films. Ting and Lee [17] prepared Cu 2-x Se nanocrystals by one-pot solution-phase method.…”
Section: Introductionmentioning
confidence: 99%